Salicylic Acid Is Involved in Rootstock–Scion Communication in Improving the Chilling Tolerance of Grafted Cucumber - Fu, Xin; Feng, Yi-Qing; Zhang, Xiao-Wei; Zhang, Yan-Yan; Bi, Huan-Gai; Ai, Xi-Zhen (Frontiers in Plant Science, 2021)
Salicylic acid has been proven to be a multifunctional signaling molecule that participates in the response of plants to abiotic stresses. Here, we used cold-sensitive cucumber and cold-tolerant pumpkin as experimental materials to examine the roles of SA in root-shoot communication responses to aerial or/and root-zone chilling stress in own-root and hetero-root grafted cucumber and pumpkin plants. The results showed that pumpkin (Cm) rootstock enhanced the chilling tolerance of grafted cucumber, as evidenced by the observed the lower levels of electrolyte leakage (EL), malondialdehyde (MDA), and higher photosynthetic rate (Pn) and gene expression of Rubisco activase (RCA). However, cucumber (Cs) rootstock decreased the chilling tolerance of grafted pumpkin. Cs/Cm plants showed an obviously increase in the mRNA expression of ICE1, CBF1 and COR47 and CBF1 protein level in leaves under 5/25 °C and 5/5 °C stress, or in roots under 25/5 °C and 5/5 °C stress, respectively compared with the Cs/Cs. Chilling stress increased the endogenous SA content and the activity of phenylalanine ammonia-lyase (PAL), and the increase in SA content and PAL activity in Cs/Cm plants were much higher than in Cs/Cs plants. Transcription profiling analysis revealed the key genes of SA biosynthesis, PAL, ICS, and SABP2 were upregulated, while SAMT, the key gene of SA metabolism was down-regulated in Cs/Cm leaves, compared with Cs/Cs leaves under chilling stress. SA accumulation in the Cs/Cm leaves was mainly attributed to an increase in SA biosynthesis in leaves, and that in transport from roots under aerial and root-zone chilling stress, respectively. In addition, exogenous SA significantly upregulated the expression level of cold responsive genes, enhanced ΦPSII, Fv/Fm and Pn, while decreased EL, MDA and CI in grafted cucumber. These results suggest that SA is involved in rootstock-scion communication, and grafting-induced chilling tolerance by upregulating the expression of cold responsive genes in cucumber plants under chilling stress.